Pediatric injury trends and relationships with social vulnerability during the COVID-19 pandemic: A multi-institutional analysis. Issue 1 (20th January 2023) - Flynn-O'Brien, Katherine T.; Collings, Amelia T.; Farazi, Manzur; Fallat, Mary E.; Minneci, Peter C.; Speck, K. Elizabeth; Van Arendonk, Kyle; Deans, Katherine J.; Falcone, Richard A.; Foley, David S.; Fraser, Jason D.; Gadepalli, Samir; et al.
Abstract : In this multi-institutional study of 9 Level 1 Pediatric Trauma Centers, there was an increased risk of pediatric injury during the first 6 months of the COVID-19 pandemic, with the most socially vulnerable children at greater risk of intentional injury. Abstract : BACKGROUND: The impact of the COVID-19 pandemic on pediatric injury, particularly relative to a community's vulnerability, is unknown. The objective of this study was to describe the change in pediatric injury during the first 6 months of the COVID-19 pandemic compared with prior years, focusing on intentional injury relative to the social vulnerability index (SVI). METHODS: All patients younger than 18 years meeting inclusion criteria for the National Trauma Data Bank between January 1, 2016, and September 30, 2020, at nine Level I pediatric trauma centers were included. The COVID cohort (children injured in the first 6 months of the pandemic) was compared with an averaged historical cohort (corresponding dates, 2016–2019). Demographic and injury characteristics and hospital-based outcomes were compared. Multivariable logistic regression was used to estimate the adjusted odds of intentional injury associated with SVI, moderated by exposure to the pandemic. Interrupted time series analysis with autoregressive integrated moving average modeling was used to predict expected injury patterns. Volume trends and observed versus expected rates of injury were analyzed. RESULTS: There were 47, 385 patients that met inclusion criteria, with 8, 991 treated in 2020 and 38, 394 treated in 2016 to 2019. The COVID cohort included 7, 068 patients and the averaged historical cohort included 5, 891 patients (SD, 472), indicating a 20% increase in pediatric injury ( p = 0.031). Penetrating injuries increased (722 [10.2%] COVID vs. 421 [8.0%] historical; p < 0.001), specifically firearm injuries (163 [2.3%] COVID vs. 105 [1.8%] historical; p = 0.043). Bicycle collisions (505 [26.3%] COVID vs. 261 [18.2%] historical; p < 0.001) and collisions on other land transportation (e.g., all-terrain vehicles) (525 [27.3%] COVID vs. 280 [19.5%] historical; p < 0.001) also increased. Overall, SVI was associated with intentional injury (odds ratio, 7.9; 95% confidence interval, 6.5–9.8), a relationship which increased during the pandemic. CONCLUSION: Pediatric injury increased during the pandemic across multiple sites and states. The relationship between increased vulnerability and intentional injury increased during the pandemic. LEVEL OF EVIDENCE: Prognostic and Epidemiological; Level III. Abstract :